Reliability of Assessing Non-severe Elevation of Intracranial Pressure Using Optic Nerve Sheath Diameter and Transcranial Doppler Parameters - Chen, Li-min; Wang, Li-juan; Shi, Lin; Chen, Hong-xiu; Jiang, Xiao-han; Chen, Qian-qian; Xing, Ying-qi (Frontiers in Neurology, 2019)
Background/Aims: Non-invasive measurement of intracranial pressure (ICP) using ultrasound has garnered increasing attention. This study aimed to compare the reliability of ultrasonographic measurement of optic nerve sheath diameter (ONSD) and transcranial doppler (TCD) in detecting potential ICP elevations. Methods: Patients who needed lumbar puncture (LP) in the Department of Neurology were recruited from December 2016 to July 2017. The ONSD and TCD measurements were completed before LP. Results: One hundred and sixty five participants (mean age, 41.96±14.64 years; 80 men; 29 patients with elevated ICP) were included in this study. The mean ICP was 170±52 mmH2O (range75–400mmH2O). Univariate analyses revealed that ICP was non-significantly associated with TCD parameters and significantly associated with ONSD (r=0.60, P<0.001). The mean ONSD of the elevated ICP group was significantly higher than that of the normal ICP group (4.53±0.40 mmvs3.97±0.23 mm; P<0.001). Multivariate linear regression determined that the difference between ICP and ONSD is significant. Conclusions: In the early stage of intracranial hypertension, ONSD is more reliable for evaluating ICP than TCD.